1999
DOI: 10.1038/sj.bjc.6690090
|View full text |Cite
|
Sign up to set email alerts
|

Low levels of cathepsin D are associated with a poor prognosis in endometrial cancer

Abstract: Total cytosolic cathepsin D (Cat D) levels were estimated by an immunoradiometric assay in a series of 156 consecutive patients with surgical stages I–III primary endometrial adenocarcinoma. Simultaneously, the tissue content of both oestrogen (ER) and progesterone (PR) receptors, and p185 HER-2/neu , DNA content (ploidy), and the fraction of S-phase cells (S-phase) were also estimated. Tumoral Cat D content ranged from 0 to 243 pmol mg −1 protein (median 44 pmol m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 41 publications
0
10
0
1
Order By: Relevance
“…The 1988 FIGO surgical staging that was used for risk stratification for more than two decades as well as complex clinicopathologic algorithms developed for therapeutic triage, lack the desired prognostic precision 4, 5, 7, 19. The need for an accurate risk stratification system for patients with endometrial cancer has motivated multiple efforts aimed at identifying prognostic biomarkers 20-27. Molecular biomarkers may potentially identify women at high risk for recurrence and death, predict response to currently available treatments and direct the development of novel targeted therapies.…”
Section: Discussionmentioning
confidence: 99%
“…The 1988 FIGO surgical staging that was used for risk stratification for more than two decades as well as complex clinicopathologic algorithms developed for therapeutic triage, lack the desired prognostic precision 4, 5, 7, 19. The need for an accurate risk stratification system for patients with endometrial cancer has motivated multiple efforts aimed at identifying prognostic biomarkers 20-27. Molecular biomarkers may potentially identify women at high risk for recurrence and death, predict response to currently available treatments and direct the development of novel targeted therapies.…”
Section: Discussionmentioning
confidence: 99%
“…The cytosolic assay is a well-standardized method for the quantification of the expression of enzymes. Falcón et al [10]reported that in stage I–III primary endometrial adenocarcinoma, patients with low cytosolic cathepsin D levels estimated by an immunoradiometric assay showed poorer survival than patients with high cathepsin D levels. On the other hand, Lösch et al [11]reported quite opposite results detected by immunohistochemical analysis in patients with stage I–III endometrial adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…The tissue was mechanically disrupted and the sub-cellular fractions (cytosolic and nuclear) were obtained as previously described [50]. DNA was extracted by a standard procedure.…”
Section: Methodsmentioning
confidence: 99%
“…Ploidy status and S-phase fraction were estimated by flow cytometry as previously reported [50]. Tumors with a DNA index > 0.9 and < 1.1 were classified as “(quasi)diploid” and others as aneuploid.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation